MONITORING OF THE STRUCTURE OF DENTOALVEOLAR ANOMALIES IN CHILDREN OF DONETSK REGION WHO SOUGHT ORTHODONTIC TREATMENT - Kobtseva, O.A.; Zabolotna, I.I.; Аvdusenko M.V.; Yarov, Yu.Yu. (World of Medicine and Biology, 2019)
The purpose of the study was to research the structure of dentoalveolar anomalies in three age groups (7-9 years, 10-12 years, and 13-15 years) in 354 children of the Donetsk region on appeal. It was established that the main reasons children aged 7-15 sought the orthodontic treatment were anomalies of individual teeth and dentition. Only 9,0 % of the total number of children complained of having malocclusion. The structure of dentoalveolar anomalies was dominated by the combined orthodontic pathology. Anomalies of individual teeth and dentition in combination with an anomaly of occlusion were detected in 79,1% (280/354) of the total number of children examined. The most common anomalies of the dentition and individual teeth were narrowing (55,1%; 195/354) and shortening of the dentition (69,2%; 245/354), the vestibular position of the incisors or canines (52,5%; 186/354) and macrodentia of the teeth (25,1%; 89/354). Early extraction of primary teeth was observed in 50% (75/150) of the examined children in group 1. The most common bite anomaly in all age groups was distal bite (53,6%; 150/280) – 44,4%, 71,4%, 48,6%, respectively.